PENGARUH LINGKUNGAN KERJA DAN KEADILAN PROSEDURAL TERHADAP DISIPLIN PEGAWAI DINAS PENDIDIKAN KABUPATEN KEPULAUAN MENTAWAI PROVINSI SUMATERA BARAT - Jottan Sakerengan Lelenggu (Universitas Negeri Jakarta, 2015)
This study aims to determine the direct influence of (1) work environment with discipline, (2) procedural fairness with discipline, (3) work environment with procedural fairness. The method used was survey method with a correlation approach. In this study used as a sample is 66 employees of education department were selected based on random techniques (simple random sampling). Data obtained by distributing questionnaires. This research was conducted in the Mentawai Islands District Education Office. Based on the hypothesis testing that has been done, it can be described as the findings of the study as follows: (1) there is a positive influence directly the work environment with discipline, (2) there is a direct positive effect of procedural justice with discipline, (3) there is a direct positive influence between environment working with procedural fairness.